No assembler required. (Economist, 2015)
The article looks at the development of toys and devices designed to teach young children about computer programming. It describes the KIBO device from KinderLab Robotics, which uses blocks with symbols that can be placed in a sequence then wirelessly uploaded to provide movement instructions to a robot. Topics include the Scratch programming tool developed by education researcher Mitchel Resnick and the question whether programming will be a widely needed skill in the future.